2020
DOI: 10.3389/fpsyg.2020.00066
|View full text |Cite
|
Sign up to set email alerts
|

Building Wellbeing in People With Chronic Conditions: A Qualitative Evaluation of an 8-Week Positive Psychotherapy Intervention for People Living With an Acquired Brain Injury

Abstract: Research indicates that Acquired Brain Injury (ABI) is associated with significant and chronic impairment across multiple areas of functioning including physical, cognitive, emotional and behavioral domains. Whilst impairments associated with ABI can be ameliorated, cure is seldom possible. The emergence of positive psychology reflects a paradigm shift in health and wellbeing research, highlighting the role of character strengths, positive emotions, meaning, and resilience. Positive psychology interventions ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 71 publications
(75 reference statements)
1
20
0
Order By: Relevance
“…The barrier ‘recovery stage’ was noted by one participant only, who felt there was one negative consequence of the ‘fun group.’ She felt that as her peers were further along in their recovery than her, she didn’t feel a part of the friendship group and their limitations made her realise that she wouldn’t return to her old self. Previous research has highlighted that psychotherapy groups should consider grouping patients according to their perceived stage in recovery ( Tulip et al, 2020 ). However, as previously noted, being in a mixed group that included service-user mentors was beneficial for most due to upward social comparison ( Festinger, 1954 ), and so grouping interventions according to recovery stage would compromise those benefits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The barrier ‘recovery stage’ was noted by one participant only, who felt there was one negative consequence of the ‘fun group.’ She felt that as her peers were further along in their recovery than her, she didn’t feel a part of the friendship group and their limitations made her realise that she wouldn’t return to her old self. Previous research has highlighted that psychotherapy groups should consider grouping patients according to their perceived stage in recovery ( Tulip et al, 2020 ). However, as previously noted, being in a mixed group that included service-user mentors was beneficial for most due to upward social comparison ( Festinger, 1954 ), and so grouping interventions according to recovery stage would compromise those benefits.…”
Section: Discussionmentioning
confidence: 99%
“…ABI patients undergoing rehabilitation during the pandemic were often unable to access face-to-face appointments or groups ( Coetzer and Bichard, 2020 ) as healthcare professionals were deployed to acute COVID-19 services ( Silva et al, 2020 ), increasing psycho-social symptoms of anxiety, isolation and apathy ( Rossi et al, 2020 ). Although brain injury can bring considerable distress and suffering, there are also potential opportunities for psychological growth ( Frankl, 1985 ; Wong, 2011 ; Lyon et al, 2020 ; Tulip et al, 2020 ). Presented here, are the qualitative experiences of ABI patients from a Neurorehabilitation service in South Wales, United Kingdom, who participated in a series of interventions designed to facilitate wellbeing during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The word "wellbeing" is not a simile for reduced illbeing, quality of life or happiness (Headey et al, 1985;Ryff et al, 2006;Westerhof and Keyes, 2010;Skevington and Böhnke, 2018). Our own work for example (Fisher et al, 2020;Tulip et al, 2020;Wilkie et al, 2021), has shown that wellbeing may be improved in neurological disorders, and in despite of significant levels of illhealth and distress. These findings reinforce Wong's dual system model of what makes life worth living (Wong, 2012).…”
Section: Complexities and Criticisms Of Wellbeingmentioning
confidence: 99%
“…17 Biofeedback has also been shown to improve impulse control difficulties, and attentional difficulties in bulimia nervosa and attention deficit hyperactivity disorder, 15 16 18 as well as symptoms of stress, anxiety and anger. 19 The focus on physiological data in the psychotherapeutic context is gaining traction [20][21][22] and has strong theoretical underpinnings. [23][24][25] Within PM, there are three mini-games: 'The face of Cronos'; 'Treasures of the sea' and 'Sign of the Magupta'.…”
mentioning
confidence: 99%